6
$\begingroup$

Minkowski's inequality says the following: For every sequence of scalars $a = (a_i)$ and $b = (b_i)$, and for $1 \leq p \leq \infty$ we have: $||a+b||_{p} \leq ||a||_{p}+ ||b||_{p}$. Note that $||x||_{p} = \left(\smash{\sum\limits_{i=1}^{\infty}} |x_i|^{p}\right)^{1/p}$. This is how I tried proving it: \begin{align*} ||a+b||^{p} &= \sum |a_k+b_k|^{p}\\\ &\leq \sum(|a_k|+|b_k|)^{p}\\\ &= \sum(|a_k|+|b_k|)^{p-1}|a_k|+ \sum(|a_k|+|b_k|)^{p-1}|b_k|. \end{align*}

From here, how would you proceed? I know that you need to use Hölder's inequality. So maybe we can bound both the sums on the RHS since they are products.

$\endgroup$
  • 1
    $\begingroup$ instead of using $\displaymath...$ you can use $$...$$ to get displayed math; and macros like \begin{align} to get aligned equations. $\endgroup$ – Arturo Magidin Jan 5 '11 at 2:02
6
$\begingroup$

Holder's Inequality would say that $$\sum |x_ky_k| \leq \left(\sum |x_k|^r\right)^{1/r}\left(\sum|y_k|^s\right)^{1/s}$$ where $\frac{1}{r}+\frac{1}{s}=1$.

Apply Holder's twice, once to each sum, using $x_k = a_k$, $y_k = (|a_k|+|b_k|)^{p-1}$ in one, and similarly in the other, with $r=p$ and $\frac{1}{s}=1-\frac{1}{p}$.

$\endgroup$
  • $\begingroup$ I think we should apply holder to $y_k=(|a_k+b_k|)^{p-1}$ and OP should not apply triangle inequality to $|a_k+b_k|^{p-1}$. Thanks $\endgroup$ – user1131274 Dec 24 '16 at 8:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.